Peningkatan Prestasi dan Kreativitas Peserta Didik Dalam Pakat dan BP Melalui Media Digital Model Discovery Learning Pada Kelas VIII SMP Negeri 13 Madiun - M. Diana Widyaningsih (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
In this research on Catholic Religious Education and Character, selecting and presenting appropriate media will help students capture and understand the material presented. In the end, you can achieve effective and efficient learning outcomes and achieve learning goals. This research is based on problems: (1)Is the use of Digital media through ModelsDiscovery Learning can it improve the learning achievement of class VIII Catholic students at SMPN 13 Madiun?; (2) What is the use of Digital media through ModelsDiscovery Learning can it increase the creativity of Catholic students in class VIII SMPN 13 Madiun?; (3) What is the use of Digital media through ModelsDiscovery Learning can support students' interest in participating in learning activities in the subjects of Catholic Religious Education and Character in class VIII SMPN 13 Madiun?. Meanwhile, the objectives of this research are: (1) Improving student learning achievement with digital media through modelsDiscovery Learning, for class VIII Catholic students at SMP Negeri 13 Madiun; (2) Increasing students' creativity with digital media through modelsDiscovery Learning, for Class VIII Catholic students at SMP Negeri 13 Madiun. (3) Increasing students' interest in Catholic Religious Education and Character Education subjects with Digital media through ModelsDiscovery Learning, for class VIII Catholic students at SMP Negeri 13 Madiun. This research used two rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The research targets were class VIII students at SMP Negeri 13 Madiun. The data obtained is in the form of formative test results, observation sheets of learning activities. Based on the results of the analysis, it is proven that (1) Application of digital learning media modelsDiscovery Learning in the subjects of Catholic Religious Education and Character Education provide quality benefits for increasing students' achievement and creativity, which is shown in students' answers which state that students enjoy learning by using digital learning media which attracts interest and motivates them to improve their learning to be better. understand and deepen the subject matter. (2) During the learning process using digital learning media modelsDiscovery Learning in the subjects of Catholic Religious Education and Character Education have a positive impact on increasing student learning achievement and students' creativity as evidenced by an increase in students' learning completeness in each cycle, namely cycle I (76.14) and continued in cycle II (80 .57).